Eldercare Policies in Japan and Scandinavia - Midford, Paul. author. aut Link
XI, 273 p.
Keywords: These essays by no means cover all areas of interest in long-term care programs, but they offer new insights (and intriguing questions for future research) about how differently policies in this important area can be carried out in different countries.